Peru's Downstream Natural Gas Sector : A Preliminary Assessment - Reinstein, David (World Bank, Washington, DC, 2013)
This study assesses the natural gas market in Peru. In the process of evaluating the downstream market, the study identifies opportunities for meeting the Government s aspirational goals with respect to energy and natural gas development, including the efficient use of natural gas in the power and other sectors, strengthening and coordinating national energy planning for the gas sector, infrastructure development and prospects for decentralization of the natural gas market in Peru, and the potential of natural gas pricing reforms for the promotion of hydroelectricity and other renewable energy sources. This report is divided into five chapters. Chapter I describes the context in which this study was prepared. Chapter II presents a history of the natural gas sector and the Government of Peru s policy objectives to increase the use of natural gas in the domestic economy. Chapter III presents potential new markets for natural gas within the present context of the natural gas industry and the Peruvian economy. Chapter IV describes findings, issues, and options for improving Peru s downstream natural gas sector, including a discussion of the consistency between the Government s objectives and its policies for the sector. Chapter V sets out the conclusions of the study.